DAMPAK BEA MASUK TINDAKAN PENGAMANAN TERHADAP IMPOR PRODUK KAIN DI INDONESIA - Al Aqilah, Muhamad Refkhi; Setiawan, Prayoga (JURNAL PERSPEKTIF BEA DAN CUKAI, 2025)
This research aims to examine the influence of the safeguard policy, exchange rates, and market share on the import volume of fabric products. The study uses monthly data from January 2019 to November 2022, covering the period before the safeguard policy until its completion. The regression model used is General Least Square with Panel-Corrected Standard Errors (PCSE) scheme. The results show that the safeguard policy and exchange rates have a significant negative effect on import volume, while market share has a significant positive effect on import volume. The implementation of the safeguard policy raises suspicions of trade diversion and circumvention in the importation of fabric products. The implication of this research is that the government can utilize the safeguard policy to protect domestic industries from the influx of imported goods while still encouraging domestic industrialization in that sector. Keywords : Safeguard. Fabric, Policy, Industrialization